O ensino da geografia, a formação do educador e educadora e as dificuldades enfrentadas nos primeiros anos de magistério - Oliveira, Maurício dos Santos de (2022)
This research is part of the Graduate Program in Geography linked to the Institute of Geography, History and Documentation - IGHD / UFMT-Cuiabá, it is part of the research line Axis Transversal: Teaching Geography and has as its general objective the analysis of the teaching of geography the training of educators, emphasizing the challenges of the beginning of their careers. Among the specific objectives, we analyze the study and systematization of the teaching of geography at the Federal University of Mato Grosso campus Cuiabá, understanding the way in which teachers and professors of the degree course in geography are trained, as well as investigating the main difficulties faced in the beginning of the career of teachers in this discipline. The research was carried out during the pandemic period caused by Covid-19, which required new methodologies to overcome adversities and achieve the proposed goals. Among the methodological actions, a constant bibliographic review and theoretical foundation were carried out, in addition to document analyzes and the application of questionnaires, which made it possible to develop a research organized into four chapters that address the studies of aspects related to training the performance of education professionals, passing through the by the National Common Curricular Base (BNCC), the teaching of geography, the training of geography teachers at UFMT Cuiabá. They also analyze what are the main difficulties in the beginning of the career of professionals in this area of knowledge and finally the geographic analyzes were carried out, showing that the teaching of geography, the training of educators and the problems at the beginning of their careers, are situations that demand countless discussions and analyses, which can bring significant improvements to the processes of formation and performance of teachers, consequently benefiting teaching and learning.